Multiplicity dependence of (multi-)strange hadron production in proton-proton collisions at √s = 13 TeV - Acharya, S.; Adamovã, D.; Adhya, S.P.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; et al. (Springer Nature, 2020)
The production rates and the transverse momentum distribution of strange hadrons at mid-rapidity (|y| < 0.5) are measured in proton-proton collisions at √s = 13 TeV as a function of the charged particle multiplicity, using the ALICE detector at the LHC. The production rates of K⁰ₛ, Λ ,, and Ω increase with the multiplicity faster than what is reported for inclusive charged particles. The increase is found to be more pronounced for hadrons with a larger strangeness content. Possible auto-correlations between the charged particles and the strange hadrons are evaluated by measuring the event-activity with charged particle multiplicity estimators covering different pseudorapidity regions. When comparing to lower energy results, the yields of strange hadrons are found to depend only on the mid-rapidity charged particle multiplicity. Several features of the data are reproduced qualitatively by general purpose QCD Monte Carlo models that take into account the effect of densely-packed QCD strings in high multiplicity collisions. However, none of the tested models reproduce the data quantitatively. This work corroborates and extends the ALICE findings on strangeness production in proton-proton collisions at 7 TeV.
Keywords: Physics; Pseudorapidity; Multiplicity (mathematics); Strangeness production; Hadron; Strangeness; Rapidity; Particle physics; Nuclear physics; Charged particle; Strange quark; Quantum chromodynamics; Large Hadron Collider; Lambda; Proton; Ion; https://purl.org/pe-repo/ocde/ford#1.03.00